The Diet of Diabetic Patients in Spain in 2008–2010: Accordance with the Main Dietary Recommendations—A Cross-Sectional Study - Muñoz-Pareja, Maritza; León-Muñoz, Luz M.; Guallar-Castillón, Pilar; Graciani, Auxiliadora; López-García, Esther; Banegas, José R.; Rodríguez-Artalejo, Fernando (PLOS ONE, 2012)
Background No previous study has assessed the diet of the diabetic patients in the general population of an entire country in Europe. This study evaluates accordance of the diet of diabetic adults in Spain with nutritional recommendations of the European Association for the Study of Diabetes (EASD), American Diabetes Association (ADA), and the Mediterranean diet (MD). Methods and Findings Cross-sectional study conducted in 2008–2010 among 12,948 persons representative of the population aged ≥18 years in Spain. Usual food consumption was assessed with a dietary history. EASD accordance was defined as ≥6 points on a score of 12 nutritional goals, ADA accordance as ≥3 points on a score of 6 goals, and MD accordance as ≥7 points on the Mediterranean Diet Adherence Screener. In the 609 diagnosed diabetic individuals, the diet was rich in saturated fat (11.2% of total energy), but trans fat intake was relatively low (1.1% energy) and monounsaturated fat intake was high (16.1% energy). Carbohydrate intake was relatively low (41.1% energy), but sugar intake was high (16.9% energy). Intake of cholesterol (322 mg/day) and sodium (3.1 g/day) was also high, while fiber intake was insufficient (23.8 g/day). EASD accordance was observed in 48.7% diabetic patients, ADA accordance in 46.3%, and MD accordance in 57.4%. The frequency of EASD, ADA and MD accordance was not statistically different between diagnosed and undiagnosed diabetic individuals. Conclusions Only about half of diabetic patients in Spain have a diet that is consistent with the major dietary recommendations. The lack of dietary differences between diagnosed and undiagnosed diabetic individuals reflects deficiencies in diabetes management.